Subgrid-scale backscatter in reacting and inert supersonic hydrogen–air turbulent mixing layers. (25th March 2014) - O'Brien, J.; Urzay, J.; Ihme, M.; Moin, P.; Saghafian, A.
Abstract This study addresses the dynamics of backscatter of kinetic energy in the context of large-eddy simulations (LES) of high-speed turbulent reacting flows. A priori analyses of direct numerical simulations (DNS) of reacting and inert supersonic, time-developing, hydrogen–air turbulent mixing layers with complex chemistry and multicomponent diffusion are conducted here in order to examine the effects of compressibility and combustion on subgrid-scale (SGS) backscatter of kinetic energy. The main characteristics of the aerothermochemical field in the mixing layer are outlined. A selfsimilar period is identified in which some of the turbulent quantities grow in a quasi-linear manner. A differential filter is applied to the DNS flow field to extract filtered quantities of relevance for the large-scale kinetic-energy budget. Spatiotemporal analyses of the flow-field statistics in the selfsimilar regime are performed, which reveal the presence of considerable amounts of SGS backscatter. The dilatation field becomes spatially intermittent as a result of the high-speed compressibility effect. In addition, the large-scale pressure-dilatation work is observed to be an essential mechanism for the local conversion of thermal and kinetic energies. A joint probability density function (PDF) of SGS dissipation and large-scale pressure-dilatation work is provided, which shows that backscatter occurs primarily in regions undergoing volumetric expansion; this implies the existence of an underlying physical mechanism that enhances the reverse energy cascade. Furthermore, effects of SGS backscatter on the Boussinesq eddy viscosity are studied, and a regime diagram demonstrating the relationship between the different energy-conversion modes and the sign of the eddy viscosity is provided along with a detailed budget of the volume fraction in each mode. A joint PDF of SGS dissipation and SGS dynamic-pressure dilatation work is calculated, which shows that high-speed compressibility effects lead to a decorrelation between SGS backscatter and negative eddy viscosities, which increases for increasingly large values of the SGS Mach number and filter width. Finally, it is found that the combustion dynamics have a marginal impact on the backscatter and flow-dilatation distributions, which are mainly dominated by the high-Mach-number effects.